TINJAUAN YURIDIS MENGENAI PERMOHONAN PAILIT PERUSAHAAN BADAN USAHA MILIK NEGARA YANG BERBENTUK PERSEROAN TERBATAS - Julivia Nur Prisintyas (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACT UUK and PKPU have regulated BUMN bankruptcy, but this is still limited to BUMN that are engaged in the public interest. The definition of a BUMN engaged in the public interest is almost the same as the definition of a Public Corporation. Apart from this, BUMN Persero is very different from Perum. BUMN Persero as stated in Article 1 point 2, is a BUMN in the form of a Limited Liability Company whose capital is divided into shares wholly or at least 51% of its shares are owned by the state whose main objective is to pursue profit. The formulation of the problem in this thesis is, what is the juridical basis related to the application for bankruptcy against a BUMN company in the form of a Limited Liability Company and what are the legal consequences if a BUMN company in the form of a Limited Liability Company goes bankrupt. The research method that I use is a normative juridical research. The results show that if the BUMN is in the form of a Persero, it does not have to be the Minister of Finance who applies for bankruptcy but it can be by the debtor himself or his creditors as stipulated in Article 2 Paragraph (1) UUK and PKPU. The legal consequence arising from bankruptcy is that the debtor loses the right to control his assets, but the legal actions in the civil sector do not stop. Keywords: Bankruptcy, State-Owned Enterprises, Limited Company